Implementasi Metode Saw Pada Sistem Pendukung Keputusan Penerima Bantuan Langsung Tunai Dana Desa (BLT-DD) - Muhammad Wahyu Rizky; Indra Kanedi; Ila Yati Beti; Arius Satoni Kurniawansyah (UNIVED Press, 2025)
In determining the recipients of direct cash assistance for village funds (BLT-DD), Karya Pelita Village still uses a manual method with village meetings. In its application, village meetings are considered less efficient and prone to conflicts of interest. This needs to be overcome with a system that can help the decision-making process quickly, accurately and fairly. The decision support system for direct cash assistance recipients of village funds uses the Simple Additive Weighting (SAW) method. The process involves determining criteria, giving weights, and normalizing data to produce a preference value that is the basis for decisions. This system is designed with PHP programming language and MySQL database. This research produces a system that is able to increase efficiency and accuracy in determining recipients of direct cash assistance for village funds, and reduce conflicts of interest. Based on the results of data testing as many as 14 alternative recipient candidates, the final results showed that 10 alternatives had the highest score and were eligible to receive assistance, and 4 other residents were declared ineligible for BLT-DD assistance.